Guide to producing statistics on time use : measuring paid and unpaid work (United Nations, 2005)
This publication presents an overview of different approaches in the design of time-use surveys. The publication provides further impetus to the development of time-use statistics and assistance to countries interested in undertaking time-use surveys. It reviews methods and practices in collecting, processing and disseminating time-use statistics through compilation of country experiences. It is also aimed at facilitating the harmonization of methods and practices in collecting, processing and disseminating time-use statistics. In addition, the publication is meant to solicit comments and suggestions on the trial International Classification of Activities for Time-Use statistics (ICATUS) which will subsequently be revised.